Respostas
respondido por:
1
Resposta:
A razão dessa PA é 3.
Explicação passo-a-passo:
Fórmula geral da PA
an=a1+(n-1)r
onde n é o termo da PA e r é a razão.
Do enunciado:
a2=9
a2=a1+(2-1)r=9 => a1+r=9 (I)
a14=45
a14=a1+(14-1)r=45 => a1+13r=45 (II)
Para resolver o sistema de (I) e (II)
(II)-(I)
a1-a1+13r-r=36
12r=36
r=36/12
r=3
respondido por:
1
resolução!
a14 = a2 + 12r
45 = 9 + 12r
45 - 9 = 12r
36 = 12r
r = 36/12
r = 3
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás